Implementación del Manual Descriptivo de Puestos para La Gran Bodega de las Frutas y Verduras - Jiménez-Guzmán, Kevin (Instituto Tecnológico de Costa Rica, 2014)
The aim of this work is the creation of a job description manual for the company “La Gran Bodega de las Frutas y Verduras”, which in its desire to improve its organization, wants to add this element as part of the human resource management. In order to carry out this investigation, it was necessary to take into account the expertise from the employees of the company in order to create the organizational chart, which was the basis for identifying each job. After identifying each position, a data collection instrument was distributed in order to gather the necessary information and create the job description manual This manual will allow the company to obtain current information about the tasks and responsibilities assigned to each position. Finally, this element will help to the management department during forthcoming recruitment and training processes, as well as jobs evaluation of every position within the company.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2014
Keywords: Puestos de trabajo; Reclutamiento; Manuales